Positive core beliefs and their relationship to eating disorder symptoms in women. - Cooper, M; Proudfoot, J (2013)
Positive core beliefs, compared with negative self or negative core beliefs, are relatively neglected in the eating disorder (ED) research literature, despite their significance in treatment. Using a sample of younger women and relevant to those who typically experience EDs, this study outlines a new measure of positive core beliefs and examines its psychometric properties. On the basis of factor analysis, two subscales were developed: positive social self beliefs and positive individual self beliefs. The measure had good internal consistency and good construct validity. Positive individual self beliefs predicted low levels of ED symptoms when confounds were controlled. Positive social self beliefs predicted low levels of depressive symptoms, when confounds were controlled. Positive core beliefs would benefit from further study in subclinical and clinical ED groups of younger women.